2012
DOI: 10.1186/1471-2334-12-168
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed initiation of antiretroviral therapy for Indian HIV-Infected individuals with tuberculosis on antituberculosis treatment

Abstract: BackgroundFor antiretroviral therapy (ART) naive human immunodeficiency virus (HIV) infected adults suffering from tuberculosis (TB), there is uncertainty about the optimal time to initiate highly active antiretroviral therapy (HAART) after starting antituberculosis treatment (ATT), in order to minimize mortality, HIV disease progression, and adverse events.MethodsIn a randomized, open label trial at All India Institute of Medical Sciences, New Delhi, India, eligible HIV positive individuals with a diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 19 publications
(19 reference statements)
0
41
0
2
Order By: Relevance
“…Experience derived from the treatment of other AIDS-defining illnesses, such as Pneumocystis jirovecii pneumonia and tuberculosis, show that prompt initiation of cART in antiretroviral-naïve patients leads to better clinical outcomes compared with deferred initiation. [46][47][48] Our findings also demonstrate evidence for better outcomes with concurrent cART and support its use even during induction chemotherapy for AIDS-related lymphomas (ARLs).…”
Section: Discussionmentioning
confidence: 54%
“…Experience derived from the treatment of other AIDS-defining illnesses, such as Pneumocystis jirovecii pneumonia and tuberculosis, show that prompt initiation of cART in antiretroviral-naïve patients leads to better clinical outcomes compared with deferred initiation. [46][47][48] Our findings also demonstrate evidence for better outcomes with concurrent cART and support its use even during induction chemotherapy for AIDS-related lymphomas (ARLs).…”
Section: Discussionmentioning
confidence: 54%
“…Three studies explicitly reported on how death was ascertained or confirmed (Table 2) [38], [39], [45].…”
Section: Resultsmentioning
confidence: 99%
“…Where all patients were initiated on ART during TB treatment, the median start times occurred in month 2 or 3 after starting TB treatment [14], [25], [27], [32], [36], [37]. The variability in reporting between studies limited our ability to examine the mortality impact of different ART initiation times with respect to the start of TB treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of TB therapy prior to the initiation of ART was shown to have an effect on the development of IRIS with longer TB treatment reducing the complication of IRIS. However, delayed HIV treatment increases the risk of all‐cause mortality leading to the recommendation of starting ART early, within 2 weeks, in patients with CD4 counts below 50 cells μ l −1 (Abdool Karim et al , ; Blanc et al , ; Havlir et al , ; Manosuthi et al , ; Sinha et al , ; Mfinanga et al , ; Amogne et al , ). It is thus anticipated that prevalence of TB‐IRIS will increase in HIV infection, making development of new preventive or treatment strategies more pressing.…”
Section: Mycobacterial Irismentioning
confidence: 99%